The level of customer satisfaction towards services cape in city campus libraries provided by higher education in Melaka, Melaka Bandaraya Bersejarah / Nur Farah Wahida Ahmad - Ahmad, Nur Farah Wahida (2014)
Library is the main reference point for all students where information can be obtained. It places to keep wide collection of sources of information. Based on the current study, the study looks for customer’s satisfaction with servicescape in libraries provided by university city campus libraries in Malacca. Data was collected through survey questionnaire. The selection of respondent obtained through data collected from questionnaire study. A convenience sampling was employed to select the respondent. This study involves descriptive research in order to describe the characteristics of variable chosen. Non-probability sampling has been chosen by the researcher to conduct this study. Statistical technique that used to analyze the data are reliability test, frequency distribution and Pearson correlation coefficient. Research conducted at UiTM and UTeM with 150 respondents. 100 respondents from UiTM library city campus and 50 respondents from UTeM Library City Campus. Based on the first objective to study the level of customer satisfaction towards services cape university city campus in Melaka. Second objective is to determine the perception of service scape toward customer satisfaction in university city campus in Melaka. The third objective was relationship between dependent and independent variables by using the correlation analysis. The fourth objective was using the coefficient analysis on the significant variable affected service scape the most.